Application of logistic regression models in observational methodology: game formats in grassroots football in initiation into football - Lapresa, Daniel; Arana, Javier; Anguera, M.Teresa; Pérez-Castellanos, J.Ignacio; Amatria, Mario (Anales de Psicología / Annals of Psychology, 2015)
This study shows how simple and multiple logistic regression can be used in observational methodology and more specifically, in the fields of physical activity and sport. We demonstrate this in a study designed to determine whether three-a-side futsal or five-a-side futsal is more suited to the needs and potential of children aged 6-to-8 years. We constructed a multiple logistic regression model to analyze use of space (depth of play) and three simple logistic regression models to determine which game format is more likely to potentiate effective technical and tactical performance.